2020
DOI: 10.1093/ofid/ofaa375
|View full text |Cite
|
Sign up to set email alerts
|

Fever Patterns, Cytokine Profiles, and Outcomes in COVID-19

Abstract: Background Prolonged fever is associated with adverse outcomes in dengue viral infection. Similar fever patterns are observed in COVID-19 with unclear significance. Methods We conducted a hospital-based case-control study of patients admitted for COVID-19 with prolonged fever (fever>7 days) and saddleback fever (recurrence of fever, lasting less than 24 hours, after defervescence beyond day 7 of illness). Fever was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…The fourth loop is the hypercoagulatory loop, which is represented by platelet count in this model. A meta-analysis of 7,613 Covid-19 patients revealed that patients with severe disease had a lower platelet count than those with non-severe disease (Jiang et al, 2020), which is in line with our data. However, not all studies have found platelet counts to be a predictor of Covid-19 mortality (Amgalan and Othman, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The fourth loop is the hypercoagulatory loop, which is represented by platelet count in this model. A meta-analysis of 7,613 Covid-19 patients revealed that patients with severe disease had a lower platelet count than those with non-severe disease (Jiang et al, 2020), which is in line with our data. However, not all studies have found platelet counts to be a predictor of Covid-19 mortality (Amgalan and Othman, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…COVID-19 patients had higher mRS scores (i.e., a higher level of disability) than individuals without COVID-19 at discharge, even though both groups shared similar baseline mRS scores ( Pilotto et al, 2020 ). Fever has been recognized as the most common symptom of hospitalized COVID-19 patients ( Benussi et al, 2020 ; Ng et al, 2020 ; Qiu et al, 2020 ; Wang et al, 2020 ). Oxygen therapy has been widely taken for COVID-19 patients ( Barrett et al, 2020 ; Hassan et al, 2020 ; Kayem et al, 2020 ; Liu et al, 2020 ; Paganini et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cases with prolonged fever were also more likely to require ICU admission (11.1% vs 0.9%; p = .05) (13).…”
Section: Discussionmentioning
confidence: 97%